2016
DOI: 10.1631/jzus.a1500345
|View full text |Cite|
|
Sign up to set email alerts
|

Typical dielectric elastomer structures: dynamics and application in structural vibration control

Abstract: Abstract:In recent years, dielectric elastomer (DE) structures have received great attention in various fields of engineering, such as artificial muscle, soft robot, resonator, and structural vibration control, due to its prominent advantages. In the present paper, the theoretical and experimental research into the dynamical behavior of DE structures and their application for vibration control is reviewed. In the theoretical research into dynamical behavior, from a mechanics viewpoint, DE structures are usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Of the 20 studies included, seven were from China [45][46][47][48][49][50][51], five were from the USA [52][53][54][55][56], and the rest were from Australia [57], Germany [58], Ireland [59], the Netherlands [60], Poland [28], Spain [61], Turkey [62], and Vietnam [63]. There were fifteen RCTs with two arms, four RCTs with three arms, and one RCT with four arms.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 20 studies included, seven were from China [45][46][47][48][49][50][51], five were from the USA [52][53][54][55][56], and the rest were from Australia [57], Germany [58], Ireland [59], the Netherlands [60], Poland [28], Spain [61], Turkey [62], and Vietnam [63]. There were fifteen RCTs with two arms, four RCTs with three arms, and one RCT with four arms.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We, therefore, mention briefly that this has led to the development of electro-viscoelastic models of different degrees of complexity with a variety of applications, as discussed variously in [79][80][81][82][83][84][85][86][87][88][89][90][91].…”
Section: (D) Viscoelasticitymentioning
confidence: 99%
“…Much of the theoretical research on dielectric elastomers is based on elasticity, and while it is our intention to focus on the elastic behaviour of dielectric materials in this paper, it is well known that their behaviour can be significantly viscoelastic and dissipative. We, therefore, mention briefly that this has led to the development of electro-viscoelastic models of different degrees of complexity with a variety of applications, as discussed variously in [79][80][81][82][83][84][85][86][87][88][89][90][91].…”
Section: (D) Viscoelasticitymentioning
confidence: 99%
“…Numerical results are selectively shown and the underlying physical mechanisms are discussed. Then, we also provide an updated account of the nonlinear dynamic analyses of DE structures, which could serve as a supplement to the earlier review of Huang et al [25]. Our last focus point here is DE phononic crystals or metamaterials, which exhibit a certain kind of periodicity in structural geometry, boundary conditions, or/and material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [24] reported a summary of the recent advances in the theory of DEs and demonstrated some examples of using the theory to design DE transducers. In contrast to the above-mentioned review papers, which all are inclined toward the constitutive behavior of DEs and the static responses of DE structures, Huang et al [25] summarized the state-of-the-art of dynamic responses and vibration controls of DE structures. The analytical models presented in The present survey, while again from the mechanics viewpoint, intends to show the advances in the study of vibrations and waves in DE structures.…”
Section: Introductionmentioning
confidence: 99%